2017
DOI: 10.1108/ijchm-09-2015-0471
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of workplace bullying among hospitality employees

Abstract: Purpose The purpose of this study is to the address the key factors of workplace bullying among hospitality employees, as workplace bullying results in damaging consequences on both individuals and organizations. Design/methodology/approach This study first defines the phenomenon of workplace bullying and then reviews the related literature. Data are collected from a sample population of 238 hospitality employees obtained from the latest European Working Conditions Survey. Logistic regression analysis is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 50 publications
(67 reference statements)
7
60
0
3
Order By: Relevance
“…Human resource planning plays a vital role in WB situations by linking the job roles in a temporal and situational manner (Cowan & Fox, 2015). According to Ariza-Montes et al (2017), responsible HRD professionals can significantly minimize the organizational levels of WB by modifying certain working conditions and setting up a supportive working environment. Handling the WB situation, the HR planners become emotional laborers as they play the role of a management advisor; an unbiased, neutral third-party investigator; as well as a mediator (Cowan & Fox, 2015).…”
Section: What Recent Wb Research Concludesmentioning
confidence: 99%
“…Human resource planning plays a vital role in WB situations by linking the job roles in a temporal and situational manner (Cowan & Fox, 2015). According to Ariza-Montes et al (2017), responsible HRD professionals can significantly minimize the organizational levels of WB by modifying certain working conditions and setting up a supportive working environment. Handling the WB situation, the HR planners become emotional laborers as they play the role of a management advisor; an unbiased, neutral third-party investigator; as well as a mediator (Cowan & Fox, 2015).…”
Section: What Recent Wb Research Concludesmentioning
confidence: 99%
“…As a result, studies have reported that WSH is a severe public health concern that affects 42% of women working in hospitality jobs in the United States [ 19 ], 74.6% in 27 European countries [ 20 ], 89% in Australia [ 21 ], 50% in the Nordic Region [ 22 ], and 60% in Taiwan [ 23 ]. It is also a significant public health issue in Sub-Saharan African hospitality workplaces, such as Accra, Ghana [ 11 , 24 ] (49.4%), Cameroon (98.8%) [ 25 ], Zimbabwe (78%) [ 8 ], and South Africa (14%) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The review developed in this paper draws on and synthesises a strong tradition of research on deviant behaviour and its links with hospitality. Hospitality is often associated with the notion of deviance and deviants: venues and resorts are frequently seen as sites for hedonistic, transgressive and criminal behaviour (Andrews, 2009;Botterill & Jones, 2010;Botterill, Pointing, Hayes-Jonkers, Clough, Jones, & Rodriguez, 2013;Botterill, Seixas, & Hoeffel, 2014;Chapman & Light, 2016); employers and operators in the sector are regularly portrayed as engaging in unethical practices (Baum, 2015;Harris, 2012;Terry, 2009); hospitality organisations and occupations are characterised as spaces of violence, harassment and bullying (Ariza-Montes, Arjona-Fuentes, Law, & Han, 2017;Meloury & Signal, 2014;Ram, 2018); and the sector itself is often treated as a marginalised profession attracting deviants and misfits (Baum, Kralj, Robinson, & Solnet, 2016;Orwell, 1989;Robinson, 2008;Wood, 1997). The topic of deviance continues to emerge in research on hospitality management (Pizam, 2012(Pizam, , 2015(Pizam, , 2016aTorres, van Niekerk, & Orlowski, 2017;Tresidder, & Martin, 2018) and in cognate fields of tourism (Li, & Chen, 2017;Tham & Wang, 2017) and services management (Bedi & Schat, 2017;Boukis, 2016).…”
Section: Introductionmentioning
confidence: 99%